Different mechanical circulatory support strategies for infarct-related cardiogenic shock: a subanalysis of the ECLS-SHOCK Trial - Feistritzer, Hans-Josef; Zeymer, Uwe; Ouarrak, Taoufik; Akın, Ibrahim; Rassaf, Tienush; Lehmann, Ralf; Eitel, Ingo; Seidler, Tim; Skurk, Carsten; Clemmensen, Peter; Voigt, Ingo; Seyfarth, Melchior; et al. (JACC Cardiovascular interventions, 2025)
Background - Mechanical circulatory support (MCS) devices are frequently used in patients with acute myocardial infarction complicated by cardiogenic shock. In clinical practice, escalation of MCS device therapy is performed in a significant proportion of patients aiming to improve hemodynamic status. - Objectives - The aim of this study was to analyze outcomes of different MCS device strategies in the ECLS-SHOCK (Extracorporeal Life Support in Cardiogenic Shock) trial. - Methods - The present subanalysis from the ECLS-SHOCK trial analyzed outcomes of patients treated with upfront extracorporeal life support (ECLS) only, bailout MCS, and escalated MCS therapy. The primary outcome was 30-day all-cause mortality. - Results - Upfront ECLS only, bailout MCS, and escalated MCS therapy were used in 165 (78.9%), 54 (26.0%), and 27 (12.9%) patients, respectively. Thirty-day all-cause mortality was 44.8% (95% CI: 37.1%-52.8%), 61.1% (95% CI: 46.9%-74.1%), and 55.6% (95% CI: 35.3%-74.5%) in the upfront ECLS, bailout MCS, and escalated MCS group (P = 0.09). Need for renal replacement therapy was higher in the bailout MCS (35.2%; 95% CI: 22.7%-49.4%) than in upfront ECLS (7.3%; 95% CI: 3.8%-12.4%) and escalated MCS (14.8%; 95% CI: 4.2%-33.8%) (P < 0.001). Moderate or severe bleeding complications were similar in the upfront ECLS (25.5%; 95% CI: 19.0%-32.8%), bailout MCS (22.2%; 95% CI: 12.0%-35.6%), and escalated MCS (22.2%; 95% CI: 8.6%-42.3%) group (P = 0.86). - Conclusions - Bailout and escalated MCS therapy is associated with numerically higher 30-day mortality compared with upfront ECLS use only. Bailout MCS use is also associated with higher need for renal replacement therapy. (Extracorporeal Life Support in Cardiogenic Shock [ECLS-SHOCK]; NCT03637205)